Image reversal resist photolithography of silicon-based platinum and silver microelectrode pattern - Nurulhaidah Daud,; Nor Farhah Razak,; Normahirah Nek Abd Rahman,; Azizah Mohd Zahidi,; Chin, Siew Xian; Tengku Elmi Azlina Tengku Muda, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Silicon-based platinum (Pt) and silver (Ag) microelectrodes are constructed using photolithography technique and used in detecting arsenic activity in different electrolytes. Pt and Ag have good properties either as a working, a counter, or a reference electrode due to their low electrical resistance, high melting point, and high chemical stability. This chemical sensor has the ability to detect the changes in the level or activity of arsenic in electrolytes. Patterning these metals by wet chemical or dry etching is not a feasible process as these metals cannot be etched properly. The lift-off process can be applied to ease the etching process, but it has a major problem whereby the metal particles or ears may remain at the edges at the end of the process. The process variables, particularly the resist slope, were investigated to reduce possible defects using an image reversal resist. The thickness and angle of the resist side wall were measured by SEM. The effects of many factors that may influence or resist steep angle formation were analyzed and optimized with the Design of Experiment (DOE) technique to achieve the target recipe of resist angle < 60°. The lower angle of the resist side wall resulted in a better percentage yield of good electrode pattern after the lift-off process. The ability of fabricated microelectrode and influence of supporting electrolytes in arsenic determination were discussed.